Frontiers in African Digital Research : Conference Proceedings - Dreiser, Anja R.; Samimi, Cyrus (2022)
In view of the developments of eSciences and accompanying infrastructures in German academia, the Cluster of Excellence Africa Multiple with its Digital Solutions portfolio has set the ambitious aim of establishing a digital research repository for its disciplinary heterogenous research projects ranging from economics to climate studies to linguistics, history and media studies, the “only” common ground being the studied area “Africa” and “African diasporas”. The four thematic sections that all touch upon eSciences, or put more generally, the digital transformation of the academic world and society from very different perspectives and disciplinary diversity. Be it knowledge management as a big data business model for academic services, digital neo-colonialism, the different legal aspects, problems of bias in semantic data processing, digitalization projects in Africa or digitization projects and collections built up in Europe.
Keywords: Digital Humanities; Digitization; African Studies; eSciences; Repositories